If `veca=hati+2hatj-hatk, vecb=2hati+hatj+hatk and vecc=5hati-4hatj+3hatk` then find the value of `(veca+vecb).vec c`

Advertisement Remove all ads

#### Solution

`veca=hati+2hatj-hatk, vecb=2hati+hatj+hatk and vecc=5hati-4hatj+3hatk`

`therefore (veca+vecb).vec c`

`=(hati+2hatj-hatk+2hati+hatj+hatk).(5hati-4hatj+3hatk)`

`=(3hati+3hatj).(5hati-4hatj+3hatk)`

=3 x 5+3 x (-4) +0 x 3

=15-12

=3

Concept: Vectors Examples and Solutions

Is there an error in this question or solution?

#### APPEARS IN

Advertisement Remove all ads